Transforming English Language Teaching Through AI: Evaluation of the Strategies and Potential of Artificial Intelligence Applications in EFL - Daulay, Silvi Fitria; Ginting, Pirman (Institut Agama Islam Negeri Palopo, 2024)
Artificial Intelligence has the capacity to transform multiple sectors, such as English Language Teaching (ELT). In recent years, academics and educators have focused on incorporating artificial Intelligence in English Language Teaching to assess its advantages and effectiveness. This study will investigate the methodologies employed in English Language Teaching (ELT) and the potential use of Artificial Intelligence on students. 30 English teachers participated in this study as responders, utilizing Artificial Intelligence, such as ChatGPT. The research design employed both quantitative and qualitative methods. Quantitative data was collected via surveys and evaluated using descriptive statistics. Qualitative data was collected through in-depth interviews and processed using thematic analysis. The findings of this study demonstrate substantial outcomes in responses collected via questionnaires and interviews. Educators concur that ChatGPT has a beneficial impact on enhancing students' English proficiency. Using ChatGPT necessitates teacher assistance. This is intended to prevent the inappropriate usage of ChatGPT for unrelated topics. Thus, it is necessary to employ suitable strategies when incorporating AI into language instruction. This research exclusively focuses on using ChatGPT with teachers, excluding students' perspectives.